2017
DOI: 10.5539/ijel.v7n4p149
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Teaching English Language in a Multilingual Setting: An Investigation at Government Girls Secondary Schools of Quetta, Baluchistan, Pakistan

Abstract: Baluchistan is a multi-linguistic and multi-ethnic province of Pakistan. In this region, the inhabitants for communication purpose speak a number of local languages such as Baluchi, Brahvi, Pashto, Saraiki, Punjabi, Urdu, Sindhi and Persian. Students who attend the government schools speak these languages. This study aimed to explore the challenges faced by the secondary school female teachers while teaching the English language in their multilingual classrooms. The purposive sampling was used and 10 governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…There was always a dominant use of the mother tongue even in the English class as evident from the students' opinion. These results are in line with the findings of Al-Mahrooqi (2012) and Rasheed (2017) whose findings indicated that a majority of the students avoid using English in the classrooms or outside the classroom for fear of being laughed at by their peers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was always a dominant use of the mother tongue even in the English class as evident from the students' opinion. These results are in line with the findings of Al-Mahrooqi (2012) and Rasheed (2017) whose findings indicated that a majority of the students avoid using English in the classrooms or outside the classroom for fear of being laughed at by their peers.…”
Section: Discussionsupporting
confidence: 92%
“…Majority of the classrooms are teacher-centered and students hardly find any chance to practice English in the classroom. Imran, Asghar and Ghani (2016) attribute this lack of proficiency in English to students' poor knowledge and incorrect use of the parts of speech and articles; Gopang, Ansari, Kulsoom and Laghari (2017) to students' anxiety of learning English language; Haider (2012) to inadequate pedagogical approach; Maldonado Garcia (2018); Panhwar, Baloch and Khan (2017) to traditional methods of teaching English and lack of proper training on the part of English teachers; and, Rasheed (2017) to multilingualism, students' weak linguistic background, lack of exposure to English, students' anxiety of English and lack of teachers' training.…”
Section: Introductionmentioning
confidence: 99%
“…The prime challenge for the English language is multilingual classrooms, facing by the teachers as well as students not only in Quetta, Pakistan but also in other parts of the globe. Due to the different local languages spoken by the students in the classroom, teachers and students have to face a number of problems because it becomes a big challenge for English teachers to deal with students speaking different languages in the classrooms [56].…”
Section: G Challenges Of English Language Learning In Pakistanmentioning
confidence: 99%
“…Multilingual classes for educators as well as learners are the primary challenge of English not only in Quetta, Pakistan but also in other parts of the sphere. Various local dialects and languages are spoken by students in the classroom, thus teachers and students have many challenges with English teachers facing a greater challenge of dealing with different language speakers in classrooms (Rasheed et al, 2017). Various challenges faced by English instructors and pupils include the ignorance of the professors, educational policy and the examination system and long curricula (Khan & Khan, 2016).…”
Section: Challenges Of English Language Learning In Pakistanmentioning
confidence: 99%